Improved Capacity of LiNi0.8Mn0.1Co0.1O2 Cathode upon Sn(IV) Doping by Facile Co-Precipitation Method - Deivamani, D.; Perumal, P. (Asian Journal of Chemistry, 2020)
Nickel rich lithium nickel manganese cobalt oxide is one of the prominent cathode materials in the field of lithium ion battery. The cathode was prepared upon doping with Sn4+ by simple co-precipitation method to develop its discharge capacity. The structural and morphological studies on the cathode material were done by X-ray diffraction and scanning electron microscopy to confirm any structural changes upon doping of Sn4+. The higher discharge capacity of 210 mAh g-1 with 89% capacity retention was achieved even after 100 cycles at C/3 rate for 0.8 mol % Sn4+ doped lithium nickel manganese cobalt oxide. The structural phase change upon cycling for Sn4+ doped and un-doped cathode was illustrated by differential plot. The ionic radius and high bond stability of Sn4+ that compares Ni2+ might be the reason to prevent structural collapse during Li+ intercalation and de-intercalation process.